ANALISIS PENGGUNAAN SECOND ACCOUNT INSTAGRAM SEBAGAI PENGUNGKAPAN DIRI DALAM PERSPEKTIF KESEHATAN MENTAL (User Berumur Dewasa Muda) - Maria Dessideria Puji Setyoaty (2023)
This study aims to find out how users express themselves using Second Account in a mental health perspective when facing the pressure of visual standardization in First Account. The method used for this research is a qualitative research method, using primary data and secondary data. Data collection techniques researchers do with interviews and documentation. Researchers used data analysis techniques from Moustakas which consisted of five steps: bracketing, phenomenological reduction, clustering, data validation, and individual textural description (ITD). The results of this study found that Second Account users interpret Second Account as a container for all special self-expressions that are evaluative in nature with a broad and intimate range of topics using video or photo media that express themselves at that time. Users get a therapist experience where there is comfort, freedom and privacy space that is always ready to accommodate the user's outpourings and pleasures or complaints, and there is also an audience that can see, view and provide feedback for perpetrators of self-disclosure. Users can also talk to themselves in order to get to know more about self-features so as to increase self-confidence and reduce self-comparison with others. One can get to know a Second Account user, whether good or bad, and the information conveyed in the Second Account contains accurate and authentic information. This makes Johari Window Second Account dominate in the Open area, where users present themselves little by little in an intense manner.